The Strategy and Tactics of Pricing / A Guide to Profitable Decision Making - Holden K. Reed; Nagle T. Thomas (Prentice Hall, 1995)
This book focuses on ideas and concepts essential to every marketer's repertoire. Preface, Acknowledgements, Strategic Pricing, Costs, Financial Analysis, Customers, Competition, Strategy, Life Cycle Pricing, Customer Negotiation, Segmented Pricing, Pricing in the Marketing Mix, Competitive Advantages, Pricing Psychology, Measuring Price Sensitivity, The Law and Ethics, Indexes.